2015
DOI: 10.1371/journal.pone.0139064
|View full text |Cite
|
Sign up to set email alerts
|

Early Exposure to Respiratory Allergens by Placental Transfer and Breastfeeding

Abstract: The relationship between allergen exposure and the onset of or protection from allergic diseases remains unclear. Many factors could be related to immunological responses, such as the age when the exposure occurs, type of allergen, timing, dose, and allergen route. In this study, we investigated whether exposure to respiratory allergens could occur in pregnancy or early life. In particular, we assessed whether Der p 1 and Blo t 5, as well as specific antibodies against these allergens, could be detected in 90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…Moreover, in the tropical and subtropical areas of the world, the importance of B. tropicalis as a cause of sensitization has been demonstrated [2,14,15,16,17] and even early life IgE responses to B. tropicalis have been reported [13,18]. Therefore, the advances in knowledge regarding the allergenicity of B. tropicalis and its profile of reactive allergens are imperative for the design of clinical interventions as well as the diagnosis of Blomia allergy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the tropical and subtropical areas of the world, the importance of B. tropicalis as a cause of sensitization has been demonstrated [2,14,15,16,17] and even early life IgE responses to B. tropicalis have been reported [13,18]. Therefore, the advances in knowledge regarding the allergenicity of B. tropicalis and its profile of reactive allergens are imperative for the design of clinical interventions as well as the diagnosis of Blomia allergy.…”
Section: Introductionmentioning
confidence: 99%
“…7 Studies in mice have examined conditions that are required to induce oral tolerance toward the food antigen ovalbumin (OVA) on its transfer through breast milk and showed that maternal milk factors such as TGF-b, vitamin A, and maternal OVA-specific IgG were required for oral tolerance induction and prevention of respiratory or food allergy. [8][9][10][11] Besides food allergens derived from the maternal diet, human milk is also a source of respiratory allergens such as Der p 1 and Blo t 5 from house dust mites (HDMs), 12,13 which are found in breast milk in the same range of concentration as dietary antigens such as OVA. 13 This observation is most probably related to the fact that most inhaled proteins are actually ingested because of respiratory tract mucociliary clearance [14][15][16] and will then follow the same route to the mammary gland as dietary antigens.…”
mentioning
confidence: 99%
“…The complete placental barrier to antibody transport in sheep contrasts with humans, rats and mice, where antibodies are transferred across the placenta (Kane & Acquah, 2009). Allergens including Der p 1, the main allergenic component of HDM, also cross the human placenta (Macchiaverni et al 2015) and could therefore potentially contribute to development of fetal allergy. The available evidence suggests that increased progeny susceptibility to allergy is induced by a maternal inflammatory state, rather than fetal exposure to allergen/s or allergen-specific antibodies.…”
Section: Discussionmentioning
confidence: 99%